A Social Description of the Damascus Document - Martens, John W. (My University, 1986)
Recent Biblical scholarship has acknowledged and stressed the sociological factors at play in the formation and continuing development of religious beliefs and in the structure of religious communities. By examining the text of the Damascus Document (CD), this thesis attempts to reconstruct the social structure of the CD community, and suggests reasons for its origins and development based on the social forces which contributed to its self-definition.
The first chapter examines the problem of deriving historical information from texts which are not strictly historical, and suggests a methodology which allows for the extraction of Social reality from religious texts. Following this, a date of origination is suggested, the historical period examined, and the origins of the community described.
The second chapter discusses the community's self-definition, and the implications this definition and a new social situation had on their belief and community structure. An analysis of the community's response is then offered. The third chapter examines modern sectarian theory in relation to the CD community. Using the information of the previous two chapters, the CD community is discussed as a sect and compared to another sectarian movement. The conclusions deal with the community's unique role in the religious fabric of ancient Palestine, and with their common role as a sect.
Missing Page 56.
Keywords: Biblical scholarship; Damascus Document; social structure; Religion; Religion